High performance nanoporous carbon from mulberry leaves (Morus alba L.) residues via microwave treatment assisted hydrothermal-carbonization for methyl orange adsorption: Kinetic, equilibrium and thermodynamic studies - Siraorarnroj, Siwat; Kaewtrakulchai, Napat; Fuji, Masayoshi; Eiad-ua, Apiluck (My University, 2022)
High performance nanoporous carbons were directly prepared from mulberry leaves (Morus alba L.) residues by the hydrothermal-carbonization with chemical reagent combined the microwave-assisted treatment. The as-purified ML porous carbon (MPC) was successfully applied for the adsorption of methyl orange, which is one of crucial waste-water pollutants left from an industrial sector. The MPC sample obtained from the hydrothermal process (200 °C, 12 h) using an activation of 15 wt% NaOH (700 °C, 2 h), and combined with microwave treatment at 700 W for 6 min, specifically exhibited micropores and mesopores in the MPC morphological structure. Accordingly, the highest SBET was approximately 791.79 m2/g with the total pore volume of 0.495 cm3/g. Moreover, the adsorption performance test of MPC was conducted by the shaking unit using 100 ppm methyl orange concentration. The MPC showed the highest methyl orange-adsorption uptake of 99% at 30 °C under an ambient pressure (1 atm). The development of mulberry leaves (Morus alba L.) residues into porous carbon exhibited a great attention for dyes adsorption with a rapid adsorption kinetic, and excellent adsorption capacity, which are a promising-characteristics for practical waste-water adsorption experiments.
Keywords: Adsorption; Hydrothermal carbonization; Methyl orange; Mulberry leaves residues; Nanoporous carbons